Sawit Kita WebApp Development: Artificial - Based E-Learning Intelligence and Community to Drive Actual Information Collaboration and Innovation of Palm Oil Farmers In Indonesia - Patricia, Ony; Wahabbi, Alif Budiman; Syafrianto, Edy; Putra, Fajar Kurnia; Andesti, Cyntia Lasmi (Indonesian Journal of Artificial Intelligence and Data Mining, 2024)
Web App development within the scope of the company is very in necessary in today's technological era. Development increasingly advanced technology is proof that the level of technology is high in the field of computer science. Data management is very important for a company companies, especially palm oil companies. A company needs a tool or system for managing and monitoring data company to be more efficient, simple, fast and precise. There fore the author designing a system to make it easier for companies to manage data palm oil plantations using a very easy Web App used. This research aims to develop the Sawit Kita Web App, an Artificial Intelligence based e-learning platform and community forpalm oil farmers in Indonesia. The Sawit Kita Web App consists of three main features, namely GPT 4 chat, e-learning modules and community platform. Chat GPT 4 is an Artificial Intelligence-based virtual assistant that can answer questions, provide suggestions, and produce creative content about oil palm cultivation with customization of data input by developer. The e-learning module is a feature that provides interactive and easy-to-understand learning materials about cultivation sustainable palm oil. The community platform is a feature that facilitate communication and collaboration between oil palm farmers and researchers, extension workers, and other related parties in a discussion forum. Target This research is to improve access and quality of information, literacy and skills, participation and collaboration, as well as productivity and well-being palm oil farmers in Indonesia. The research method used is method research and development with stages of analysis, design, development, implementation, and evaluation. This research is expected to provide contribution to the development of the oil palm plantation sector in Indonesia.